Spatiotemporal analysis of the activity of residential development in Poland - Cellmer, Radosław; Bełej, Mirosław (International Conference “Environmental Engineering”, 2017)
The objective of the study presented in the article is to determine the spatial diversification and determinants of construction activity in Poland between 2006 and 2015. Theoretical hypotheses and observations of behaviour of economic entities clearly show that their decisions depend both on the situation in local and regional markets, as well as distances from other regions or local markets. The number and the surface area of completed residential units, as well as the number of completed buildings and issued construction permits, were adopted as the measures of construction activity. The analysis also includes selected demographic, social and economic indices characterising the individual territorial units in Poland on the basis of the local data bank maintained by the Central Statistical Office. In the course of the study, spatial panel models were used, and as a result of the study, construction activity models were obtained, taking spatial interactions into account.
Keywords: housing activity; panel data analysis; spatial modelling